(untitled) (The Insight, 2023)
Introduction: The primary objective of this research was to understand the perception of medical students regarding the teaching and learning methods of pharmacology in a medical college associated with a tertiary care hospital. Methods and Materials: A questionnaire-based study was conducted among 3rd phase of MBBS & 2nd phase BDS students at the MH Samorita Medical College. The questionnaire, consisting of 22 pre-validated points, was carefully designed to assess the students’ views on various teaching and learning approaches. Results: The analysis was carried out on a sample of 150 medical students from the tertiary care hospital. The results indicated that 80% of the participants preferred faculty members to employ more Audio-Visual aids to enhance their learning experience. Additionally, 78.67% of the students advocated for the inclusion of case-based learning in the curriculum, while 86.67% expressed a desire for more clinical pharmacology content. Interestingly, 28% of the students felt that MCQs (Multiple Choice Questions) should be incorporated into the assessment of academic performance. As for the ideal teaching method, 13.33% of the students believed that didactic lectures were the most effective. Moreover, a majority of 65% considered the combination of an LCD projector and a blackboard as the ideal teaching/learning medium for pharmacology. Conclusions: This study highlights the preferred teaching and learning methods in pharmacology that would contribute to the overall improvement of students’ learning experiences.